2002
DOI: 10.1007/pl00011221
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study on Silicone Breast Implants and the Silicone-Related Symptom Complex

Abstract: This cohort study prospectively evaluated the prevalence of the silicone-related symptom complex (SRSC) in relation to antinuclear antibodies (ANA) and magnetic resonance imaging (MRI) of silicone breast implants (SBI) 1 year after implantation. A total of 57 women undergoing mastectomy followed by immediate breast reconstruction (IBR) and SBI between March 1995 and March 1997 at the University Hospital Rotterdam/Daniel den Hoed Cancer Centre, were prospectively evaluated. Just before and 1 year after IBR the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Contant et al [23] prospectively evaluated a cohort of 57 women with silicone-related symptom complex that were seen in an breast cancer centre between March 1995 and March 1997, who presented with sicca symptoms (dry eyes and dry mouth), arthralgias/arthritis, Raynaud’s phenomenon, headache, dizziness, memory difficulties, palpitations, diarrhoea and transpiration.…”
Section: Discussionmentioning
confidence: 99%
“…Contant et al [23] prospectively evaluated a cohort of 57 women with silicone-related symptom complex that were seen in an breast cancer centre between March 1995 and March 1997, who presented with sicca symptoms (dry eyes and dry mouth), arthralgias/arthritis, Raynaud’s phenomenon, headache, dizziness, memory difficulties, palpitations, diarrhoea and transpiration.…”
Section: Discussionmentioning
confidence: 99%
“…We included studies discussing patients with breast implants (silicone- or saline-filled) who reported or presented with silicone-related complaints (Table 1) after insertion of the breast implants and who underwent explantation of the breast implant [4, 69]. Studies of all type were included, meaning case reports, case series, case–control studies and descriptive cohort studies.…”
Section: Methodsmentioning
confidence: 99%
“…Data from a cross-sectional real-world analysis matching woman who underwent silicone breast implants and autoimmune disorders, highlighted an association between this procedure and SS [ 25 ]. In another study the authors found that patients complained more SS-related symptoms at one-year follow-up after breast reconstruction even if there was no correlation with autoantibodies or imaging (magnetic resonance) changes of the implants [ 85 ]. Indeed, in an autoimmune setting, jumping into a patient who has recently undergone breast implant surgery can sporadically occur.…”
Section: Classical Examples Of the Asia Syndromementioning
confidence: 99%